Exploring The Role Of Wordwall As A Learning Media For Teaching Procedural Texts To Ninth-Grade Students - Masliha Alfiatul Aqliyah; Sofura Azhar; Lidia Nur Aini; Indah Putri Lestari; Dian Novita (P3I UMSurabaya, 2024)
Teaching reading skills is an important part of learning English. The study aims to describe the use of the Wordwall application to teach reading comprehension to ninth-grade students. This research is conducted at one of the private schools in Sidoarjo, East Java, Indonesia using a descriptive qualitative method. The data is collected through observation and interviews. The results show that using the Wordwall media can help students comprehend the procedural text material more effectively. Based on the researchers’ observations in classroom learning, students find it easier to read and understand procedural text with the Wordwall media. Additionally, through interviews conducted to gather the students’ opinions, it is found that using the Wordwall media can create an active learning atmosphere, making students more engaged and finding it easier to read English texts.